2014
DOI: 10.2147/ijn.s58397
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidogenic effects and DNA oxidation induced in vitro by differently sized gold nanoparticles

Abstract: Gold nanoparticles (Au NPs) are used in many fields, including biomedical applications; however, no conclusive information on their potential cytotoxicity and genotoxicity mechanisms is available. For this reason, experiments in human primary lymphocytes and murine macrophages (Raw264.7) were performed exposing cells to spherical citrate-capped Au NPs with two different nominal diameters (5 nm and 15 nm). The proliferative activity, mitotic, apoptotic, and necrotic markers, as well as chromosomal damage were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 53 publications
3
29
0
2
Order By: Relevance
“…As described by Fenech (13), Di Bucchianico et al . (14) and the OECD guideline 487 (15), 1000 cells were scored to evaluate cytostasis as a reduction of replication index of the treated cells compared to the negative control. The number of apoptotic, necrotic and mitotic cells per 1000 cells was also evaluated as a measure of cytotoxicity and cell proliferation.…”
Section: Methodsmentioning
confidence: 99%
“…As described by Fenech (13), Di Bucchianico et al . (14) and the OECD guideline 487 (15), 1000 cells were scored to evaluate cytostasis as a reduction of replication index of the treated cells compared to the negative control. The number of apoptotic, necrotic and mitotic cells per 1000 cells was also evaluated as a measure of cytotoxicity and cell proliferation.…”
Section: Methodsmentioning
confidence: 99%
“…Citrate-coated Au NPs with sizes of 5 nm and 15 nm inhibit the proliferation of human primary lymphocytes and murine macrophages (Raw264.7). The reason was that Au NPs are able to trigger damage in chromosomes and apoptosis [116]. Moreover, 30 nm PEG-capped Au NPs can be further modified by arginine–glycine–aspartic acid peptide (RGD) and nuclear localization signal (NLS) peptide (RGD/NLS–Au NPs).…”
Section: Interaction Of Au Nps With Cellsmentioning
confidence: 99%
“…Very recently, Bucchianico and coauthors have studied the interactions of human primary lymphocytes and murine macrophages (RAW264.7) with di®erent sizes of spherical citrate-capped Au NPs (D core ¼ 5 nm and 15 nm). 61 They showed a size-independent correlation between the cytotoxicity of Au NPs and their tested mass concentration or absolute number, and genotoxic e®ects which were more severe for Au NP (D core ¼ 15 nm) compared to Au NP (D core ¼ 5 nm). They also found that the spherical citrate-capped Au NPs are able to inhibit cell proliferation by apoptosis and to induce chromosomal damage, in particular chromosome mis-segregation.…”
Section: The Size and Shape E®ectsmentioning
confidence: 96%